Associative Cognitive CREED for Successful Grammar Learning - Susanto, Andrias Tri (Widya Mandala Surabaya Catholic University, 2016)
This research article reports a qualitative study which was conducted to investigate ways successful EFL learners learned English grammar. The subjects of this research were eight successful EFL learners from six different countries in Asia: China, Indonesia, Japan, South Korea, Thailand, and Vietnam. The data was collected by interviewing each subject in person individually at an agreed time and place. The result showed that all the grammar learning processes described by the subjects were closely linked to the framework of Associative Cognitive CREED. There were also some contributing factors that could be integrally combined salient to the overall grammar learning process. However, interestingly, each subject emphasized different aspects of learning.